EP902 Single port access laparoscopic staging surgery in patient with early stage ovarian cancer. (1st November 2019) - Lee, S-H; Park, JS; Kim, YT; Kim, SW
Abstract : Introduction/Background: With an increase in demand for less-invasive surgeries, the role of laparoscopic surgery in the management of gynecological cancers continues to expand. However, the scope of single port laparoscopy is still limited in ovarian cancer. We reported the experience of single port access (SPA) laparoscopic staging of early stage ovarian cancer. Methodology: We prospectively collected data on women who had SPA laparoscopic staging surgery at Severance Hospital between 2014 and 2017. The surgical outcomes, including intra-operative data, time to interval between the end of SPA laparoscopy and postoperative adjuvant chemotherapy (POAC), and port related complications were measured. Results: Fifty six patients underwent SPA laparoscopic staging surgery. Mean patient age and BMI were 47.25±13.93 and 23.58 kg/m 2 ±3.24, respectively. Mean operation time was 235±93 minutes and median blood loss was 55 ml (range, 10–1100). Median time interval between the end of procedure and the start of POAC was 21 days (range, 14–31). Additional port was needed in 4 cases (7.1%) and the conversion rate to laparotomy was 8.9%. There were no peri-operative moderate to severe complications, including port-site metastasis. The upstaging rate after SPA laparoscopic staging surgery was 30.3% and POAC was performed in 34 cases (60.7%). The overall rate of recurrence with a median follow up period of 26 months was 16% (9 cases) and 4 patients died due to the disease. Conclusion: The surgical outcomes of SPA laparoscopic staging surgery in patient with early stage ovarian cancer is feasible and could be compatible with conventional laparoscopic approach in terms of operative outcomes and upstaging rate in comparison with previous studies. Disclosure: Nothing to disclose.